Soy protein isolate-sodium alginate colloidal particles for improving the stability of high internal phase Pickering emulsions: Effects of mass ratios - Zhi Wang; Yubo Zhao; Haotian Liu; Qian Chen; Qian Liu; Baohua Kong (Food Chemistry: X, 2024)
The potential of sodium alginate (SA) at different mass ratios to improve the emulsifying ability of soy protein isolate (SPI) in high internal phase Pickering emulsions (HIPPEs) was evaluated in this work. SPI-SA particles were used as a natural particle stabilizer of HIPPEs with 80 % oil phase. The properties of particles with varying SPI to SA ratios (10:0, 10:1, 10:3, 10:5, 10:10, and 10:15 w/w) were evaluated. HIPPEs with a 10:10 SPI to SA ratio exhibited the smallest droplet sizes. Both the storage modulus and loss modulus of the HIPPEs increased with increasing SA addition ratios, implying that HIPPEs with higher SA addition have stronger gel characteristics. In addition, super-resolution microscopy and cryogenic scanning electron microscopy indicated that SA addition strengthened the compactness of the interface film and increased the distribution uniformity of HIPPEs. In conclusion, the combination of SPI and SA is beneficial for improving the performance of HIPPEs.